Legal advocacy in the Roman world - Crook, John A. 1921-2007 (Cornell Univ. Pr., 1995)
J. A. Crook here examines the role and significance of the advocate in the Roman legal system. Offering comparisons with modern legal practice, he addresses such questions as why Romans used advocates, what social function advocates fulfilled, and what conclusions can be drawn about a society that required litigants to have their cases presented by someone other than themselves. Crook first provides an overview of the general function of advocacy in both Roman and modern jurisprudence. In the light of the characteristically fierce rhetorical combat waged by Roman advocates, Crook compares the status of rhetoric in Roman times and today. He then considers differences between the legal orders of ancient Rome and classical Greece. Next, he explores evidence provided by the Egyptian papyri and discusses the treatment of advocacy in classical accounts, particularly in Quintilian. In conclusion, he surveys the historical record concerning advocacy in Rome.
Keywords: Advocatuur; Romeins recht; Justice, Administration of (Roman law); Practice of law (Roman law); Procedure (Roman law); Rechtssystem; Rechtsanwalt; Geschichte; Römisches Reich